INFLUENCE OF BLADE AND PROFILE CHARACTERISTICS ON HYDRODYNAMIC EFFICIENCY OF MARINE PROPELLERS - Korol, Y. M.; Kornelyuk, O. M. (Science and Transport Progress, 2017)
Purpose.The study involves: 1) formation of 3D propeller models under study; 2) studying of the effect of profiling the blade of the propeller on its hydrodynamic characteristics; 3) development of a methodology for specifying optimal project parameters for modeling the operation of a propeller in free water, which in the future could be recommended when simulating similar tasks in the CFD package Flow Vision. Methodology. The technology of design of propellers of new series was developed. For the first time, the project methodology was proposed in the CFD package Flow Vision for studying the operation of a propeller in free water. Findings. On the example of solving a practical problem for studying the influence of blade profiling on the efficiency of a propeller, the expediency of developing the proposed methodology for setting a propeller design in the CFD package Flow Vision is justified. The using of this technique makes it possible to obtain reliable values of the propeller hydrodynamic characteristics for constructing its action curves, and also to reduce the estimated time. This approach makes it possible to optimize the process of designing propellers. Originality. Through numerous experiments and based on the analysis of the obtained results, it was found that the profiling of the propeller mainly affects its hydrodynamic characteristics. The choice and calculation of the propeller for the projected vessel occurs in the early stages of design. Therefore, the rationale for choosing one or another geometry of the marine propeller is a topical task. A method for specifying project parameters for conducting numerical experiments in studying the operation of propellers in free water was proposed and justified. Thus, it is possible to design not only the serial screws, but also the new series propellers, minimizing the costs of carrying out the research along with the reliability of the resulting calculation results. Practical value. Authors established that the influence of the propeller blade profiling on its hydrodynamic characteristics is greater than the influence of its other general and blade characteristics. The developed design methodology for the calculation of propellers in the CFD package Flow Vision can be used to design the marine propellers of both new series and existing ones, and also in the case of optimizing the shape of the propeller to ensure the greatest efficiency. The application of the technique will allow reducing the time for conducting a numerical experiment due to the convergence of the solution in a relatively short time.